Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1556/avet.55.2007.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterisation of Pasteurella multocida strains isolated from pigs in Hungary

Abstract: A total of 146 Pasteurella multocida strains isolated from swine in Hungary in the last 20 years were examined. Biochemical characterisation and PCRbased techniques were used to determine species, subspecies, biovar, capsule type and presence of the toxA gene. Eighty-seven percent of the isolates belonged to P. multocida ssp. multocida, and 98% of these had biovar 3 or were trehalose-or lactose-fermenting or ornithine decarboxylase negative variants of that. Ten percent of the strains were P. multocida ssp. se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
3
9
2
1
Order By: Relevance
“…On the other hand, although the determination of biovars is based on several (9-12) fermentation characters, the majority of the strains have been reported to belong only to a low number of biovars. Biovar 3 was shown to be the most common biovar, the presence of which seems largely independent of the host species (Fegan et al, 1995;Blackall et al, 1997Blackall et al, , 1998Townsend et al, 1998;Varga et al, 2007). In our study, biochemical fermentation patterns identified 7 different biovars (Table 2).…”
Section: Resultssupporting
confidence: 59%
“…On the other hand, although the determination of biovars is based on several (9-12) fermentation characters, the majority of the strains have been reported to belong only to a low number of biovars. Biovar 3 was shown to be the most common biovar, the presence of which seems largely independent of the host species (Fegan et al, 1995;Blackall et al, 1997Blackall et al, , 1998Townsend et al, 1998;Varga et al, 2007). In our study, biochemical fermentation patterns identified 7 different biovars (Table 2).…”
Section: Resultssupporting
confidence: 59%
“…Sixteen PMT-negative and 8 PMT-positive strains were isolated from swine suffering from pneumonia. The strains had been characterised for other phenotypic and genotypic features earlier (Varga et al, 2007;Sellyei et al, 2008).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Bisgaard et al (3) determined the subspecies by their carbohydrate fermentation patterns. Based on the diversity to fermentation of different carbohydrates, Fegan et al (13) described 10 biovars among Pm strains, and later Blackall et al (4) added four other biovars to the classification system (37).…”
mentioning
confidence: 99%